Prevalence of Solitary Thyroid Nodule in Patients Admitted in Hospital of Dera Ismail Khan, KPK, Pakistan - Rasif Khan, Rashed Ali Khan, Shahid Shehzad, Muhammad Naeem, Fouzia Jameel, Jaweria Gul, (Pakistan Journal of Medical & Health Sciences, 2022)
Solitary nodules are a typical thyroid disease appearance. Solitary thyroid nodules are little swellings that are ordinarily impalpable glands. Solitary thyroid nodules are typically benign. With a mean age of 35 years, ladies are more likely than males to develop cancer (10–20%). An endocrine gland called the thyroid is located in the lower front and sides of the neck. Its primary purpose is to regulate basal metabolic rate. It also promotes somatic and psychic growth and is crucial for calcium metabolism. The identification, examination, and treatment of thyroid nodules can be difficult. These lumps frequently develop near the thyroid gland's border and are enormous in size, causing them to feel or seem like a lump in front of the neck. A multitude of variables, including age, sex, food, iodine deficiency, and even therapeutic and ambient radiation exposure, affect the occurrence of these nodules in a given population. This study was conducted in hospital of Dera Ismail Khan, KPK,Pakistan to determine the prevalence of solitary thyroid nodules in patinets admitted in the hospital. The results indicates that females between the ages of 26 and 30 are more likely to have thyroid nodules. Swelling at the front of the lower neck is the most frequent presenting ailment. The majority of patients presented between 6 months and 3 years after the edoema first appeared. The sensitivity and specificity of FNAC in the current investigation were 92% and 98%, respectively, while sensitivity and specificity of USG were 70 and 90%, respectively. Histopathology verified all malignant tumours on FNAC, demonstrating its superiority. USG and FNAC aids in proper management planning as a result, preventing the need for additional surgery. Keywords: Solitary thyroid nodule; Thyroid neoplasm; Neck swelling; Body mass index; Pakistan